Quality assessment of harvested rainwater from green roofs under tropical climate. Issue 1 (2nd January 2016) - Sultana, Nilufa; Akib, Shatirah; Aqeel Ashraf, Muhammad; Roseli Zainal Abidin, Mohamed
Abstract: With respect to the current vulnerable climatic condition, water quality has become a matter of the highest worldwide concern. Rainwater harvesting is the most acceptable solution for overcoming this problem. Among various rainwater harvesting systems, green roof rainwater harvesting is a significant tool for improving the standard of living for rapidly growing populations in the whole world, in terms of both water demand and protecting the environment from pollution. This paper assesses the water quality parameter (dissolved oxygen (DO), pH, conductivity, and temperature) of rainwater harvesting from green roofs in humid tropic center under tropical climate conditions. It shows that the values of electric conductivity are always within Class I according to Interim National Water Quality Standards (INWQS) and Water Quality Index (WQI). Depletions of DO and pH values were observed for the green roof runoff, and the runoff quality ranged between Class I and III under INWQS and WQI. Lower value of pH indicates that harvested rainwater from green roofs is more acidic than the standard neutral value. Harvested water must be processed through general water treatment methods like filtration, disinfection, and through reverse osmosis storage tank. The indoor temperatures are always within an acceptable range.